2008
DOI: 10.1097/yco.0b013e3282f2dfca
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden in anxiety disorders

Abstract: Available limited data indicates an adverse impact on families looking after their relatives with anxiety disorders such as obsessive-compulsive disorder and posttraumatic stress disorder. There is an urgent need for further research to increase our understanding of family burden and, accordingly, to support families involved in the care of patients with anxiety disorders. The impact of caregiver burden on disease and recovery in anxiety disorders also needs to be addressed in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 31 publications
1
20
0
7
Order By: Relevance
“…Kalra, Kamath, Trivedi, and Janca (2008) reviewed the available evidence on caregivers' burden in different anxiety disorders. They found that there was a significant lack of data on anxiety disorders other than obsessive-compulsive disorder (OCD) and y Professor.…”
Section: Introductionmentioning
confidence: 99%
“…Kalra, Kamath, Trivedi, and Janca (2008) reviewed the available evidence on caregivers' burden in different anxiety disorders. They found that there was a significant lack of data on anxiety disorders other than obsessive-compulsive disorder (OCD) and y Professor.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above considerations, we suggest that the experience of Bedouin wives living with husbands who are suffering from PTSD is probably better described by the familiar concept of burden of care, which has only minimally been studied among families coping with anxiety disorders (Kalra, Kamath, Trivedi, & Janca, 2008). Similar to vicarious traumatization, caretakers' burden is described in terms of its emotional, psychological, and physical impact, as well as the experience of shame, embarrassment, feelings of guilt and self-blame (Goff, Crow, Reisbig, & Hamilton, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…(16,(36)(37)(38)(39)(40) Apesar da sua natureza crônica e incapacitante e dos altos níveis de incidência populacional, ainda é escasso o número de estudos sobre participação familiar e apoio impactante no tratamento de pacientes com transtornos de ansiedade. Porém, resultados de pesquisas relacionados a sintomas compulsivo-obsessivos e estresse pós-traumático (41) confirmam que a participação familiar é eficaz no tratamento daqueles pacientes. (42) Mesmo com SMAD, Rev.…”
Section: Psicoeducação E Família: Visão Geral Atual E Perspectivas Deunclassified
“…2017;13(1):52-59. evidência comprovada que esse tipo de intervenção é eficaz em transtornos de ansiedade, outras patologias relacionadas a esse transtorno, como por exemplo o síndrome de fobia social, ainda são ignoradas. (41) Dadas todas estas considerações, o apoio dos familiares atualmente é o fator mais importante para facilitar a recuperação do paciente psiquiátrico. Esse apoio pode ser realizado através da participação da família em um programa psicoeducacional, cujo estudo científico comprovou consistência para esse propósito.…”
Section: Psicoeducação E Família: Visão Geral Atual E Perspectivas Deunclassified